Urban internationalism: Coventry, Kiel, reconstruction and the role of cities in British–German reconciliation, 1945–1949 - Christoph Laucht (Urban History, 2024)
This article addresses the beginnings of the twinning relationship between Coventry and Kiel to introduce and exemplify the idea of ‘urban internationalism’ as a new lens onto urban histories of town twinning initiatives and a contribution to the historiography of British town twinning. Focusing on paradiplomatic initiatives by municipal officials, religious dignitaries and other citizens in Coventry and Kiel, the article examines the role that cities played in British–German reconstruction and reconciliation in the period from the end of World War II until the formation of the Federal Republic of Germany in 1949.